Radioimmunotherapy for the treatment of head and neck cancer. Issue 8 (August 2019) - Karam, Sana D; Raben, David
Summary: Evidence to date shows that immune checkpoint inhibitors have little benefit in most patients with head and neck squamous cell carcinoma (HNSCC). Intense interest is focused on identifying and developing rational combinations of immune checkpoint inhibitors and different therapeutic interventions to enhance response rates and overcome immune checkpoint inhibitor resistance. Combining radiotherapy, a primary HNSCC treatment modality, with immunotherapy has been shown to induce potent antitumour immune responses in many cancers including HNSCC. In addition to its direct cytotoxic effect on the cancer cell, radiotherapy can shape the tumour microenvironment to affect the abundance and composition of tumour-infiltrating immune cells and therefore change responses to immune checkpoint inhibitor therapy. In this Series paper, we examine how radiotherapy can be used to its maximum therapeutic potential in the setting of immunotherapy treatment for HNSCC by focusing on published clinical and preclinical data. We rely on preclinical evidence for this disease to discuss how radiotherapy can help create and maintain an immunologically permissive environment. Our hope is that such mechanistic insights will provide a foundation for maximising the use of radioimmunotherapy in disease control, designing future trials, interpreting emerging immunotherapy data, and accelerating discovery within radioimmunotherapy interventions for HNSCC.